Case Report: Potential Role of Corticosteroids in the Management of Post-COVID-19 Pneumonia - Aissaoui, Houari; Eskenazi, Anaïs; Suteau, Valentin; Adenis, Antoine; Drak Alsibai, Kinan (Frontiers in Medicine, 2021)
Certain patients who recover from severe pneumonia due to coronavirus disease 2019 (COVID-19) remain symptomatic in the post-infectious period, either clinically, radiologically, or respiratory. The post-COVID-19 period is characterized by clinical symptoms of varying duration from one subject to another and does not seem to depend on the severity of initial pneumonia. The persisting inflammatory and/or immune reactions in the post-COVID-19 period may play a role in the development of pulmonary lesions. Here, we report the case of a 61-year-old man with severe COVID-19 pneumonia, complicated by acute respiratory distress syndrome and pulmonary embolism, which required the patient's admission to the intensive care unit and high-flow oxygen therapy. The patient was hospitalized for 23 days for the management of his severe COVID-19 pneumonia. Afterwards, he was discharged home following a negative SARS-CoV-2 PCR test. The post-COVID-19 period was characterized by a complex respiratory symptomatology associating cough, resting dyspnea, and exertional dyspnea requiring oxygen therapy for several weeks. Surprisingly, the follow-up chest CT scan performed 4 weeks after discharge revealed bilateral interstitial lung lesions. After ruling out pulmonary superinfection, the patient was treated with oral corticosteroid for 3 months at a digressive dose. In our case, the use of corticosteroid therapy in the post-COVID19 phase had improved the outcome of the lung disease. These benefits are characterized by a rapid symptomatic improvement, accelerated repair of pulmonary images, rapid oxygen withdrawal, and rapid return to daily activities.